1989
DOI: 10.1007/bf02441491
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of elastic properties in the urethral flow controlling zone by signal analysis of urodynamic pressure/flow data

Abstract: When urethral flow is treated as a lossless flow through an elastic tube, the relationship between the detrusor pressure and the urinary flow can be related to the elasticity of the flow-controlling zone of the urethra. A recent analytical method of describing urethral elasticity is implemented on a computer. The function p(Q) = pmo + LmQm is fitted to the recorded pressure/flow data. p(Q) is the detrusor pressure, Q the flow and pmo, m and Lm parameters. The elastic properties are then obtained as p(A) = pmo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

1990
1990
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
0
10
2
Order By: Relevance
“…These methods included computerised models as described by Sch/~fer [21][22][23], Spangberg et al [30], Terio et al [31] and Mastrigt and Rollema [18]. Nielsen and coauthors find that these models are too complicated and cumbersome for daily urological practice.…”
Section: Similarities With Other Methodsmentioning
confidence: 99%
“…These methods included computerised models as described by Sch/~fer [21][22][23], Spangberg et al [30], Terio et al [31] and Mastrigt and Rollema [18]. Nielsen and coauthors find that these models are too complicated and cumbersome for daily urological practice.…”
Section: Similarities With Other Methodsmentioning
confidence: 99%
“…The use of more degrees of freedom, for example, parameters, within an approximation method will likely result in a more accurate method, albeit at increased algorithmic complexity. In the past, any extension beyond a linear fit was found to be not reproducible and not of added value for describing the PURR 14 . However, we showed that a linear fit is rather inaccurate when only based on p detQmax , as all (linear) one‐parameter methods were found significantly less accurate in predicting p muo when compared to the three‐parameter method.…”
Section: Discussionmentioning
confidence: 64%
“…It is true that the reproducibility of the exponent m is far from perfect; however, this parameter is not randomly distributed since the patients tend to have the same shape of urethral resistance relations after performing several micturitions [14,16]. It is true that the reproducibility of the exponent m is far from perfect; however, this parameter is not randomly distributed since the patients tend to have the same shape of urethral resistance relations after performing several micturitions [14,16].…”
Section: Discussionmentioning
confidence: 99%